FAKTOR-FAKTOR YANG BERPERAN DALAM KEBERSYUKURAN (GRATITUDE) PADA ORANGTUA ANAK BERKEBUTUHAN KHUSUS PERSPEKTIF PSIKOLOGI ISLAM - Adang Hambali; Asti Meiza; Irfan Fahmi (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2015)
This study aimed to explore of what factors that influencing gratitude of Muslim parents who having children with special needs. This study was a preliminary stage to develop an instrument of specific gratitude. The research methods used literature study and qualitative approach by in-depth interview. The subjects were six couple of parent from childrens with special needs. The result found that there were differences as well as similarities about concept of gratitude between Western perspective and Islam particularly in term of appreciation and expression. Gratitude emerged to respond something acquired covering things, happiness moments, ability to cope difficulties, and weaknesses. There was also having added value namely spiritual experience that pushed motive to getting closer toward Alloh SWT. Positive feeling and emotion emerged such as kindhearted, positive thinking, and optimistic in facing the life.